WHAT EXPLAINS THE RECENT JOBLESS RECOVERIES?. (18th January 2016) - Panovska, Irina B.
Abstract : This paper considers a correlated unobserved-components model for output, employment, and hours in order to disentangle the causes for the last three jobless recoveries. The composition of the structural shocks during recessions and the periods immediately following recessions has changed, as have the responses of employment and hours to those shocks. Recessions before 1984 were followed by recoveries driven by positive permanent shocks to output, whereas post-1984 recessions were followed by weak recoveries in demand. Employment is more sensitive to demand shocks post-1984, leading to weak recoveries in employment. In addition, hours and employment were complements before 1984, but are treated as substitutes after 1984. Much of the initial decrease in demand is now absorbed on the intensive margin.